Size and Development of the Shadow Economy and of Do-it-Yourself Activities: The Case of Germany - Andreas Buhn; Alexander Karmann; Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2007)
This paper presents the first MIMIC (multiple indicator multiple causes) model estimate of the size and development of the shadow economy and of do-it-yourself (DIY) activities in Germany from 1970 to 2005. By 2005, they reached a level of about 17% and 4.94%. While the shadow economy has regularly increased over the years, DIY activities - though quite sizeable - have remained more or less constant since the early 1990s. The driving forces for the shadow economy are regulation and tax burden whereas for DIY activities, the level of unemployment is the main factor.
Keywords: O17; O5; D78; H2; H11; H26; 330; Shadow economy; Do-it-yourself activities; Tax burden; Regulation; Domestic currency in circulation; Unemployment; MIMIC models